2020
DOI: 10.1055/s-0040-1701526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Freedom for One-and-a-Half Nostril, Mononostril, and Binostril Endoscopic Endonasal Transsphenoidal Approaches

Abstract: Objective This article determines which of the one-and-a-half nostril, mononostril, and binostril endoscopic endonasal transsphenoidal approaches provide a superior manipulation during surgery. Methods The three approaches were orderly performed on 10 silicon-injected cadaveric heads to quantitatively assess surgical freedom and attack angle for sella. Measurements were determined with a standardized method under neuronavigation system using data of computed tomography. Results The one-and-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, these methods have the advantage of knowing the physiologically neutral globe position, a major limitation of previous cadaveric studies using desiccated tissue. 11,[24][25][26][27] In addition, this VR model provides the ability to use much large sample sizes than that seen with these cadaveric studies. The VR model is also unique in that it provides submillimetric precision when performing measurements in a 3-dimensional space, beyond the 3 planes available with most imaging software.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods have the advantage of knowing the physiologically neutral globe position, a major limitation of previous cadaveric studies using desiccated tissue. 11,[24][25][26][27] In addition, this VR model provides the ability to use much large sample sizes than that seen with these cadaveric studies. The VR model is also unique in that it provides submillimetric precision when performing measurements in a 3-dimensional space, beyond the 3 planes available with most imaging software.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared surgical freedom and working angles between OETA and BETA in cadaveric dissection ( 10 ). The results showed that the OETA had similar surgical freedom and working angles to the BETA for most anatomic targets in the sellar or parasellar region.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, we introduced the one-and-a-half nostril endoscopic transsphenoidal approach (OETA) with the expectation of combining the advantages of the binostril and mononostril approaches ( 9 ). This approach provided superior exposure and surgical freedom and caused less damage to the nasal septum ( 10 ).…”
Section: Introductionmentioning
confidence: 99%